Strategi Guru Bimbingan Dan Konseling Dalam Pencegahan Dan Penanganan Perundungan Siswa Di Sekolah - Nadya Insanty Camilia; Muhammad Zainal Mutaqqin; Patricia Masyayu Sekar Pinanti; Yunita Najwa Salim (Fakultas Pertanian, 2026)
This study aims to provide an in-depth description of the strategies employed by Guidance and Counseling (GC) teachers in the prevention and management of bullying within the school environment. A descriptive qualitative approach was adopted, utilizing interviews, observations, and documentation as the primary methods of data collection. The findings reveal that GC teachers hold a pivotal role in fostering a safe and supportive school climate through the implementation of both preventive and curative interventions. Preventive measures include counseling outreach activities, anti-bullying campaigns, social–emotional learning initiatives, and collaborative efforts with subject teachers and homeroom teachers. In contrast, the handling of bullying incidents involves comprehensive assessments, individual and group counseling, the application of restorative disciplinary practices, and continuous guidance provided to both victims and perpetrators. The study also identifies several challenges, such as limited parental involvement and insufficient understanding of bullying among certain members of the school community. Overall, the results underscore that the effectiveness of bullying prevention and intervention efforts depends on collective engagement from all stakeholders and the reinforcement of a positive school culture aimed at cultivating empathy, tolerance, and responsibility among students.